Noble-metal-free heterojunction photocatalyst for selective CO2 reduction to methane upon induced strain relaxation - Das, Risov; Sarkar, Shreya; Kumar, Ritesh; Ramarao, Seethiraju D.; Cherevotan, Arjun; Jasil, Mohammed; Vinod, Chathakudath P.; Singh, Abhishek Kumar; Peter, Sebastian C. (ACS Catalysis, 2022)
Sunlight-driven CO2 hydrogenation has drawn tremendous attention. However, selective CH4 formation via CO2 photoreduction is very challenging. Herein, we report a metal oxide semiconductor heterojunction consisting of BiVO4 and WO3 as a photocatalyst for the efficient conversion of carbon dioxide (CO2) selectively to methane (105 mu mol g(-1) h(-1)) under visible light in the absence of a sacrificial agent. Wise selection of the reaction medium and the strategically tuned heterojunction upon strain relaxation suppresses the competitive hydrogen generation reaction. The detailed photophysical, photoelectrochemical, and X-ray absorption spectroscopy studies pointed to the Z-scheme mechanism of electron transfer, which favors superior electron and hole separation compared to the individual components of the composite catalyst and other well-known photocatalysts reported for CO2 reduction. The observations are further corroborated by experimental diffuse reflectance infrared Fourier transform spectroscopy and theoretical density-functional theory calculations, which reveal that the heterojunction has a lower free-energy barrier for CO2 conversion to CH4 due to the larger stabilization of the *CH2O intermediate on the strain-relaxed heterojunction surface, in comparison to the pristine BiVO4 surface. The present work provides fundamental insights for constructing high-performance heterojunction photocatalysts for the selective conversion of CO2 to desired chemicals and fuels.
Keywords: CO2 reduction; heterostructure; methane; Photocatalysis; Z-scheme

Intrinsic charge polarization in Bi19S27Cl3 nanorods promotes selective C-C coupling reaction during photoreduction of CO2 to ethanol - Das, Kousik; Das, Risov; Riyaz, Mohd; Parui, Arko; Bagchi, Debabrata; Singh, Ashutosh Kumar; Singh, Abhishek Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (Advanced Materials, 2023)
Obtaining multi-carbon products via CO2 photoreduction is a major catalytic challenge involving multielectron-mediated C-C bond formation. Complex design of multicomponent interfaces that are exploited to achieve this chemical transformation, often leads to untraceable deleterious changes in the interfacial chemical environment affecting CO2 conversion efficiency and product selectivity. Alternatively, robust metal centers having asymmetric charge distribution can effectuate C-C coupling reaction through the stabilization of intermediates, for desired product selectivity. However, generating inherent charge distribution in a single component catalyst is a difficult material design challenge. Here, a novel photocatalyst, Bi19S27Cl3, is presented which selectively converts CO2 to a C-2 product, ethanol, in high yield under visible light irradiation. Structural analysis through transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy reveals the presence of charge polarized bismuth centers in Bi19S27Cl3. The intrinsic electric field induced by charge polarized bismuth centers renders better separation efficiency of photogenerated electron-hole pair. Furthermore, charge polarized centers yield better adsorption of CO* intermediate and accelerate the rate determining C-C coupling step through the formation of OCCOH intermediate. Formation of these intermediates is experimentally mapped by in situ Fourier-transform infrared spectroscopy and further confirmed by theoretical calculation.
Keywords: C-C coupling; charge polarization; CO2 reduction; Ethanol; Photocatalysis